Mechanical testing on welded pipes - Yeo, C.C (Universiti Malaysia Sarawak, UNIMAS, 2010)
Welding plays an indispensable role in many industries especially the pipe welding and welded joint has become one of the most important joining methods available nowadays. Hence, it is essential to understand the mechanical properties of the welded joint for pipe so that the welding pipe can be applied effectively in various kinds of industries. The aim of this project is to investigate the strength of the welded pipe which is determined by mechanical testing based on ASME Standard Code. Tension test and three point bending test are conducted to characterize and gain greater understanding of welded joint mechanical properties and quality. The results of the welded pipe and base metal pipe are then interpreted and compared in terms of strength, strain, and maximum load before failure of test specimen to differentiate and investigate the effect of base metal pipe after being welded. Results and analysis indicate that the welded pipe has slightly higher strength than the base metal pipe in both of the mechanical tests. The base metal pipe shows a slightly increase of stiffness after being welded but has been reduced in ductility. Overall, based on the results, it shows that the welded joint is as strong as, or even stronger than the base metal pipe and has similar mechanical behavior with base metal pipe. The experiment also shows that the improper preparation of welded joint will weaken the strength of the welded pipe and will cause the failure for passing the mechanical testing.